Comparative Analysis of Solar Charge Controller Performance Between MPPT and PWM on Solar Panels - Akbar Satria Putra; Hasti Afianti; Richa Watiasih (Fakultas Teknik Universitas Bhayangkara, 2022)
Solar power plants require other supporting equipment besides solar panels, including SCC (Solar ChargerController) for solar panel charger media to batteries. While the battery itself as a store of electrical energy generatedby solar panels. Therefore, other supporting equipment is very important in the application of solar power generationsystems.In the charger system or battery charging on solar panels, an SCC solar charger controller is needed as the chargermedia. In the solar charger controller there are two types between MPPT (Maximum Power Point Tracker) and PWM(Pulse Width Modulation). This study aims to analyze the performance comparison between SCC which is good forsolar panels in battery charging. Apart from the comparison tool, the simulation tool used in this study is which oneis superior between MPPT and PWM. The way of comparison is to compare the current and voltage results obtainedfrom the SCC input and output between MPPT and PWM to find out which one is superior.The results of the comparison with simulation produce current input from MPPT between 10, 15, 20, 25 A while PWMinput current is between 10, 15, 20, 15A. The results of the MPPT current output are between 12, 18, 21, 25A, whilethe PWM output current is between 8, 18, 21, 25A. For the MPPT input voltage results are between 29, 25, 36, 41V,while the PWM is between 26, 29, 36, 41V, while the output MPPT voltage is between 14, 14, 15, 15V, while the PWMis in the range of 14, 14, 15, 15V.